The Effectiveness of Using the Smart Application (Sistem Manajemen dan Analisa Rekening Terpadu) on Employee Performance at Perumda Air Minum Tirta Buana Bojonegoro - Kurniawan, Bima Wahyu; Nugroho, Rusdi Hidayat (Business and Investment Review, 2024)
Digital transformation has become a critical necessity for companies to enhance operational efficiency and service quality. Perumda Air Minum Tirta Buana Bojonegoro employs the SMART application (Sistem Manajemen dan Analisa Rekening Terpadu) to support employee performance in managing customer data, reducing errors, and improving service speed. This study aims to evaluate the effectiveness of the SMART application on employee performance using a descriptive qualitative approach through interviews with employees. The results show that the SMART application accelerates work processes, reduces error rates, and supports the delivery of more optimal customer services. Improved efficiency and accuracy have also positively impacted customer satisfaction and the company's reputation. The SMART application has proven to be a strategic step in supporting the company's sustainable digital transformation.